Dependence of Nonlinear Response and Magnon Scattering on Damping - Tao Qu; Aneesh Venugopal; Randall Victora (IEEE Journal of Microwaves, 2021)
A previous theoretical model of 3-magnon scattering is connected to experimentally measured characteristics, such as the damping constant α and the power threshold, through a realistic micromagnetic simulation. Both the critical magnon amplitude and relaxation rate are determined to be proportional to α which implies that the power threshold scales sensitively as α4. In addition, the scattered magnons are found to form two sets of symmetric wavevector k ≠ 0 magnon pairs, which are focused over a small range of angles and robust for a wide power range. Our results increase understanding of the model with respect to experimental and engineering aspects, and reduce the trial and error approach to application design.